Chronic Effects of Dietary Pesticides on the Gut Microbiome and Neurodevelopment - Gama, Jessica; Neves, Bianca; Pereira, Antonio (Frontiers in Microbiology, 2022)
Many agricultural pesticides include substances that are known to be harmful to human health and while some have been banned from developed countries, they are still being used in developing countries such as Brazil. Recent studies have shown that low-level chronic dietary exposure to pesticides can affect the human gut microbiota. This possible hazardous effect of pesticides on human health has not been specifically recognized by government regulatory agencies. In Brazil, for instance, of the 10 best-selling active ingredients in pesticides in 2019, two are considered extremely toxic, Paraquat and Chlorpyrifos. Even though Paraquat has been banned in Brazil since 2020, the values of maximum residue limits (MRLs) of toxic pesticides allowed in the country are still higher than in other countries. Unfortunately, many developing countries still lack the resources and expertise needed to monitor adequately and systematically the presence of pesticide residues on food. In this work, we raise awareness to the danger the chronic exposure to high dietary levels of pesticides can pose to the public, especially considering their prolonged effects on the gut microbiome.